A novel antimicrobial peptide derived from fish goose type lysozyme disrupts the membrane of Salmonella enterica. Issue 2 (December 2015) - Kumaresan, Venkatesh; Bhatt, Prasanth; Ganesh, Munuswamy-Ramanujam; Harikrishnan, Ramasamy; Arasu, MariadhasValan; Al-Dhabi, Naif Abdullah; Pasupuleti, Mukesh; Marimuthu, Kasi; Arockiaraj, Jesu
Highlights: Two AMPs, IK12 and TS10 were synthesized from murrel G-lysozyme. Antibiogram showed IK12 was active against Salmonella enterica. IK12 induced loss of cell viability in the bacterial pathogen. Membrane disruption of IK12 was confirmed by SEM. Abstract: In aquaculture, accumulation of antibiotics resulted in development of resistance among bacterial pathogens. Consequently, it became mandatory to find alternative to synthetic antibiotics. Antimicrobial peptides (AMPs) which are described as evolutionary ancient weapons have been considered as promising alternates in recent years. In this study, a novel antimicrobial peptide had been derived from goose type lysozyme (LyzG) which was identified from the cDNA library of freshwater fish Channa striatus ( Cs ). The identified lysozyme cDNA contains 585 nucleotides which encodes a protein of 194 amino acids. Cs LyzG was closely related to Siniperca chuatsi with 92.8% homology. The depicted protein sequence contained a GEWL domain with conserved GLMQ motif, 7 active residues and 2 catalytic residues. Gene expression analysis revealed that Cs LyzG was distributed in major immune organs with highest expression in head kidney. Results of temporal expression analysis after bacterial ( Aeromonas hydrophila ) and fungal ( Aphanomyces invadans ) challenges indicated a stimulant-dependent expression pattern of Cs LyzG. Two antimicrobial peptides IK12 and TS10 were identified from Cs LyzG and synthesized. Antibiogram showed that IK12 was active against Salmonella enterica, a major multi-drug resistant (MDR) bacterial pathogen which produces beta lactamase. The IK12 induced loss of cell viability in the bacterial pathogen. Flow cytometry assay revealed that IK12 disrupt the membrane of S. enterica which is confirmed by scanning electron microscope (SEM) analysis that reveals blebs around the bacterial cell membrane. Conclusively, Cs LyzG is a potential innate immune component and the identified antimicrobial peptide has great caliber to be used as an ecofriendly antibacterial substance in aquaculture.